Influence of Basal Salts, Sucrose and Plant Growth Regulator Levels on Nucellar Embryogenesis and Plantlet Regeneration in Monoembryonic Mango Varieties - Solangi, Najamuddin; Mushtaque Ahmed Jatoi; Mirani, Abdul Aziz; Waheed Ali Mirbahar; Solangi, Muhammad Aslam; Abul-Soad, Adel Ahmed; Markhand, Ghulam Sarwar (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The current study described stage-wise protocols for in vitro propagation of commercially important varieties of mango. Induction of somatic embryos (SE) and plantlet regeneration was obtained using nucellar explants of three superior monoembryonic mango vars.‘Saroli’, ‘Langra’, and ‘Chaunsa’ were cultivated in Khairpur, Pakistan. The immature fruits (2.5-4.0 cm long) were surface disinfected using 30 % sodium hypochlorite (NaOCl) solution. Results revealed that significantly highest direct somatic embryogenesis (93 %) was obtained in var. ‘Chaunsa’ under full dark on culture medium comprising of 2.0 mg L-1 N6 2-isopentenyl adenine (2iP), 0.5 mg L-1 2,4 dichlorophenoxyacetic acid (2,4-D). Medium consisted of 2iP 4.0 mg L-1, 2,4-D 1.0 mg L-1 induced significantly highest embryogenic callus (91 %) using nucellar explants in var.‘Chaunsa’. Significantly highest germination (95 %) of SE was achieved in var. ‘Chaunsa’ on the medium comprising of microsalts of MS, macrosalts of B5, 2iP 0.1 mg L-1, Kinetin (Kin) 0.5 mg L-1. Highest shoot length (5.1 cm) and root length (4 cm) were obtained in var. ‘Langra’ on the medium consisted of microsalts of MS, macrosalts of B5, 30 g L-1 sucrose, 200 mg L-1 activated charcoal (AC), 0.1 mg L-1 naphthalene acetic acid (NAA), 0.2 mg L-1 benzyl adenine (BA). Stage-wise protocols established for the regeneration of plantlets can be useful for micropropagation of the other mango varieties of the world.